Contribui??es ao estudo sobre sensoriamento espectral baseado em autovalor para aplica??es em sistemas de r?dio cognitivo - Scudeler Neto, Jo?o (2011)
The scenario of spectrum scarcity resulting from the fixed allocation policy adopted by regulatory governmental agencies has motivated research efforts which demonstrated that, although most of the frequency spectrum is already allocated, significant under-utilization exists. In this context emerged the revolutionary Cognitive Radio concept, which is expected to be a new Big Bang in wireless communications. Among its functionalities, spectrum sensing is one of the most important. Thanks to spectrum sensing, it is possible to exploit the underutilized spectrum opportunistically. The most common sensing techniques available in the literature and the challenges associated with their implementation will be discussed here. Among the most recent and promising techniques, the eigenvalue-based cooperative detection is the main focus of this thesis.